Experimental Investigation of Resin Produced with PET Applied to the Surface of Wooden Fence Posts (International Journal of Geoscience, Engineering and Technology, 2024)
Polyethylene terephthalate (PET) stands out as a recyclable material of great importance, its versatility makes it a valuable resource in industry, ensuring the conservation of natural resources and the minimization of waste when disposed of correctly. The search for an alternative method to increase the useful life of wood used as fence posts is necessary given the current use of toxic materials, such as the use of Copper-Chromium-Arsenic (CCA), a material harmful to humans and the environment. In this sense, this work presents the development of a polymeric resin, obtained through the depolymerization process, from PET discarded with a glycerin solution. The resin resulting from depolymerization, once applied to the surface of eucalyptus (Eucalyptus Cloeziana), in proportions of 4:1 (PET: Glycerin), presented a texture similar to a varnish and, after drying, proved to be efficient in protecting of wood. The field tests carried out revealed that, even though the resin applied to some test bodies had peeled off, the wood absorbed a much smaller amount of water when compared to wood not coated with resin, regardless of whether the wood was treated or not previously with CCA.